Thermal optimisation of metal hydride reactors for thermal energy storage applications - Dong, Dehua; Humphries, Terry; Sheppard, Drew; Stansby, B.; Paskevicius, Mark; Sofianos, M.; Chaudhary, A.; Dornheim, M.; Buckley, Craig (Royal Society of Chemistry, 2017)
Metal hydrides (MHs) are promising candidates as thermal energy storage (TES) materials for concentrated solar thermal applications. A key requirement for this technology is a high temperature heat transfer fluid (HTF) that can deliver heat to the MHs for storage during the day, and remove heat at night time to produce electricity. In this study, supercritical water was used as a HTF to heat a prototype thermochemical heat storage reactor filled with MgH2 powder during H2 sorption, rather than electrical heating of the MH reactor. This is beneficial as the HTF flows through a coil of tubing embedded within the MH bed and is hence in better contact with the MgH2 powder. This internal heating mode produces a more uniform temperature distribution within the reactor by increasing the heat exchange surface area and reducing the characteristic heat exchange distances. Moreover, supercritical water can be implemented as a heat carrier for the entire thermal energy system within a concentrating solar thermal plant, from the receiver, through the heat storage system, and also within a conventional turbine-driven electric power generation system. Thus, the total system energy efficiency can be improved by minimising HTF heat exchangers.